The Influence of the Use of VR-Based Learning Media on Learning Outcomes and Learning Motivation of Students in Science Learning for Class IV SDN Sadeng 03 - Aziz, Nur; Astuti, Tri; Handayani, Nova Dwi; Widyasepti, Rebecca Amellya; Bright, Fatimah Nurussyifa Clever; Nadila, Kania Yosa (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study aims to determine the effect of using Virtual Reality (VR) media on students' understanding and motivation to learn in learning Natural and Social Sciences (IPAS). The study was conducted with a quantitative approach using the ex post facto method, where researchers did not provide direct treatment, but analyzed data based on events that had occurred. The research subjects consisted of 16 students, with data collected through observation and questionnaires. The results of the analysis showed that 75% of students felt the benefits of using VR media in understanding IPAS material, while the other 25% showed doubts. In addition, the increase in IPAS scores that exceeded the Learning Objective Completion Criteria (KKTP) was also an indicator of the positive influence of VR media. In terms of learning motivation, 87.5% of students felt more motivated to use VR media, while the other 12.5% were doubtful. These findings indicate that VR media contributes to improving the quality of IPAS learning, both from the cognitive and affective aspects of students.